2015
DOI: 10.4321/s1135-57272015000200010
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de la infección por Bartonella henselae en la Comunidad Valenciana durante el período 2009-2012

Abstract: Carmen Fernández-Arias (1), María Borrás-Máñez (2), Javier Colomina-Rodríguez (2), María Cuenca-Torres (3) and Antonio Guerrero-Espejo (1,3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Moreover, there is molecular evidence of this infection in a recently described dog with generalised pyogranulomatous disease and hyperviscosity syndrome [18]. Several reports have confirmed that Bartonella infection is present in people in the Valencian Community and Catalonia (Spain) [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is molecular evidence of this infection in a recently described dog with generalised pyogranulomatous disease and hyperviscosity syndrome [18]. Several reports have confirmed that Bartonella infection is present in people in the Valencian Community and Catalonia (Spain) [19, 20]. …”
Section: Discussionmentioning
confidence: 99%